Episyenites in meta-granitoids of the Tauern Window (Eastern Alps): unpredictable?. (November 2016) - Pennacchioni, Giorgio; Ceccato, Alberto; Fioretti, Anna Maria; Mazzoli, Claudio; Zorzi, Federico; Ferretti, Patrizia
Highlights: We present maps of episyenite from glaciated outcrops of the Tauern meta-granitoids. Episyenite occurs as local static overprint of pre-existing small-displacement faults. The thickness of episyenite does not scale with fracture spatial density and fault slip. δ 18 O of calcite filling the episyenite porosity shows an influence of meteoric fluids. Abstract: The core of the Tauern tectonic window (Eastern Alps) consists of pre-Alpine granitoids (∼295 Ma) variably deformed during Alpine (∼30 Ma) amphibolite-facies metamorphism. Episyenites occur as local alteration haloes (as wide as a few meters) surrounding steeply dipping, strike-slip faults, with offsets <1 m, overprinting the metamorphic deformation structures. Episyenites are well recognizable in the field by their macroscopic porosity, ranging between 25–35 vol% (meta-granodiorite) and 13% (meta-aplite), mainly derived from dissolution of quartz. Glacier-polished outcrops allow the detailed investigation of the relationships between the episyenites and the structure of the associated faults. Field mapping indicates that episyenites: (i) are spatially linked to pre-existing faults and statically overprinted these structures; (ii) are discontinuous along faults; (iii) have a thickness (of as much as a few meters) that does not correlate with either the amount of slip along the pre-existing faults or the spatial density of the fracture network; (iv) developed with a similar extent in rocks with conspicuous variations of the original quartz grain size and structure. The studied outcrop includes a relatively large volume of episyenite associated with faults. However, despite the pervasiveness of faulting, episyenites are rare in the Tauern meta-granitoids. This localized occurrence of episyenite is inferred to represent a section of a vertical pipe structure exploiting a portion of the fault network. Our study indicates that the location and the extent of episyenite alteration cannot be simply predicted from the geometry and the fracturing patterns of the pre-existing cataclastic faults. Quartz dissolution during episyenitization was accompanied and/or followed by: (i) pervasive substitution of oligoclase and biotite/chlorite of the meta-granodiorite by albite and vermicular chlorite, respectively; and (ii) precipitation of adularia, albite, anatase, calcite, hematite and zeolites within pores. Isotopic data from the calcite filling of the pores suggest a surficial source of fluids associated with this calcite precipitation (δ 18 O (SMOW) ≈−2‰ and −3‰). In contrast, fluids syn-kinematic with the older episodes of fluid-rock interaction, during faulting and ductile shearing, had a deeper origin (δ 18 O (SMOW) ≈8–9‰). In the structural history, episyenite marks the transition from diffuse deformation to almost rigid-block behaviour of the Tauern tectonic unit, during progressive exhumation and cooling (at T <300 °C). This transition reflects the transfer of deformation to localized slip along the Brenner extensional detachment.